Factors affecting distribution of dose in horizontal direction during irradiation - Cho, Chang-Ho; Kim, Jeong-Lae; Kang, GeonUk (Edelweiss Applied Science and Technology, 2024)
Recording and managing the dose of x-rays in an x-ray machine is an important part of the data. In addition, recording and managing radiation dose data in x-ray devices plays an important role in providing transparency of radiation dose to medical staff and patients by quantifying the radiation dose data. Four mobile diagnostic X-ray units were used to analyze the dose by spatial location. The dose distribution by location was analyzed by identifying and analyzing the dose by angle for both image intensifier and flat panel detector types. The three-dimensional space of the radiation area consisted of 27 sides, and the structure of the space was assumed to be horizontal X, Y, and Z sides and vertical A, B, and C sides, and the dose analysis was performed at the assumed position. On the longitudinal side, the highest dose tissue (highest μSv/min) is B_Center : (R.B.M, Colon, Lung, Stomach, Breasts, Remainder of body) - 330.404 μSv/min, and the lowest dose tissue (lowest μSv/min) is 0.002 μSv/min on the (Skin, Bone surface, Salivary glands, Brain) side at C_270°. The findings from diagnostic X-ray devices have emphasized the importance of managing radiation exposure when using the devices and may raise questions about the management of radiation protection measures to protect the health of healthcare personnel and patients. This can be expected to advance the organization of the use of radiation devices in a safe healthcare environment. A system for managing data will be useful as an indicator to guide medical staff using the equipment and patients participating in procedures and surgeries where they can minimize their dose and avoid harm.